2018
DOI: 10.3168/jds.2017-14217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified atmosphere packaging on the growth of spoilage microorganisms and Listeria monocytogenes on fresh cheese

Abstract: Queso Fresco has a limited shelf life and has been shown to support the rapid growth of Listeria monocytogenes during refrigerated storage. In addition to improving quality and extending shelf life, modified atmosphere packaging (MAP) has been used to control the growth of pathogenic microorganisms in foods. The objectives of this study were to determine the effects of MAP conditions on the survival and growth of spoilage microorganisms and L. monocytogenes during storage of Queso Fresco manufactured without s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…Results are compatible with other studies, since, as LAB are typically facultative anaerobes, it has been reported that MAP may proportionate favorable conditions to LAB growth due to the lack of oxygen in the packaging (Khoshgozaran et al, 2012). Similar behavior was observed for MAP Queso fresco (Brown et al., 2018). In contrast, when considering Mozzarella cheese aerobically stored, it was observed a decrease in the LAB population upon storage (Akarca et al., 2015; Eliot et al., 1998).…”
Section: Resultssupporting
confidence: 81%
“…Results are compatible with other studies, since, as LAB are typically facultative anaerobes, it has been reported that MAP may proportionate favorable conditions to LAB growth due to the lack of oxygen in the packaging (Khoshgozaran et al, 2012). Similar behavior was observed for MAP Queso fresco (Brown et al., 2018). In contrast, when considering Mozzarella cheese aerobically stored, it was observed a decrease in the LAB population upon storage (Akarca et al., 2015; Eliot et al., 1998).…”
Section: Resultssupporting
confidence: 81%
“…This product was examined twice: first, samples collected in two different seasons, and then the samples used as control during the industrial trial. In the 30 cheese samples, selected after the end of the shelf life from both summer and autumn periods of production, psychotropic Gram-negative bacteria, Enterobacteriaceae and Pseudomonas , represented the dominant population of spoiled cheeses, as already observed [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 77%
“…The increasing demand of low-salt and low-fat cheese requires new hurdle technologies approaches to reduce the spoilage microbial communities along the shelf life, particularly by psychotropic Gram-negative bacteria [ 33 , 34 ] that can also trigger antimicrobial resistances [ 35 ]. To address this issue, this study focused on the characterization of the spoilage microbiota of these dairy products and the appraisal of lactic acid bacteria adjunct cultures in limiting the outgrowth of these undesirable microorganisms and consequently cheese defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen is majorly responsible for cheese spoilage as its presence facilitates the growth of aerobic microorganisms, oxidation of cheese components, nutritional value decline, off-flavors generation, unacceptable color changes, shelf-life reduction and decrease in food safety [32]. Therefore, control of oxygen content inside cheese package is of prime importance.…”
Section: Oxygen Scavengersmentioning
confidence: 99%